Application of Problem Based Learning to Enhance Students’ Problem Solving Ability in Static Fluid - Yusal, Yulianti; Nurazmi, Nurazmi; Harnipa, Harnipa (Kasuari: Physics Education Journal (KPEJ), 2023)
One of the skills needed to face challenges in the 21st century is problem solving. The purpose of this study was to find out whether there was a significant difference between students' problem solving abilities before and after applying problem based learning to static fluid material. The method used in this research is a pre-experimental method with one group pretest-posttest group design. The research subject used in this study was one of the Senior High Schools in South Sulawesi, with a total of 33 students including 9 boys and 14 girls. The instrument used to collect data is a problem solving ability test instrument in the form of a description of static fluid material. The results of the descriptive analysis showed that the average score of students' problem solving abilities before the application of problem based learning was 59.81 while after the application of problem based learning was 194.15. Meanwhile, the results of the value of the paired t-test analysis, namely 0.00 <0.05 so that Ho was rejected and H1 was accepted. Thus, there is a significant difference between students' problem solving abilities before and after the application of problem based learning to static fluid material.